Synthesis and Characterization of Cathode Material for Secondary Magnesium Batteries - Sun, Jian-Zhi (Asian Journal of Chemistry, 2011)
In this work, a cathode material for secondary magnesium batteries MgMnSiO4 was synthesized via sol-gel method. TG-DTA, XRD, IR, SEM were used to characterize the reaction and product. The results showed that the product is well-crystalline and gets small particle size. Simulation cells were assembled employing the product as positive electrode. The initial discharge capacity for MgMnSiO4 is 95 mAh g-1 and it shows great promise for secondary batteries.